2006
DOI: 10.1111/j.0038-4941.2006.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

State Growth Management and Housing Prices*

Abstract: Objective. In the United States, growth regulations aimed at environmental protection and better‐quality urban areas have become very popular since the 1960s. Although many studies have examined the housing‐price effects of local and regional growth management regulations, none has examined the effects of a state law. Past research has also tended to be cross‐sectional, rather than longitudinal, and has frequently ignored alternate hypotheses that could explain housing‐price trends. The research presented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In addition, there are many empirical studies have shown that land use regulations, including those designed based on smart growth principles pushed up housing prices and reduced housing affordability (Anthony, 2003(Anthony, & 2006. A direct result is that the economic barriers become even higher for medium-low and low-income households to live in neighborhoods with better amenities that smart growth policies helped to create.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are many empirical studies have shown that land use regulations, including those designed based on smart growth principles pushed up housing prices and reduced housing affordability (Anthony, 2003(Anthony, & 2006. A direct result is that the economic barriers become even higher for medium-low and low-income households to live in neighborhoods with better amenities that smart growth policies helped to create.…”
Section: Discussionmentioning
confidence: 99%
“…3 See, for example, reviews by Nelson et al (2004) and Quigley & Rosenthal (2005). Additional works include Anthony (2003Anthony ( , 2006, Ihlanfeldt (2009), and Meck & MacKinnon (2009). 4 We also coded the housing elements for an alternative measure of strength toward affordable housing, based on the broad implementation policy areas listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In general, growth management is an element of community-wide developmental regulation and controls disordered land development to prevent environmental pollution and solve urban sprawl (Anthony 2006;Nelson et al 2002). That is, growth management is a rational focus on local land-use regulation with a community needs based policy decision making process (Down 2004;Feiock 2004).…”
Section: Growth Management and Land-use Regulationmentioning
confidence: 99%